Current Development of Therapeutic Vaccines in Lung Cancer - Jesus Salvador Flores Banda; Sanjana Gangane; Fatima Raza; Erminia Massarelli (Vaccines)
Cancer vaccines have a potential to change the current landscape of immunotherapy research and development. They target and neutralize specific tumor cells by utilizing the body’s own immune system which offers a promising modality in treating various cancers including lung cancer. Historically, prior vaccination approaches specifically towards lung cancer have posed several challenges but also potential with early phase I/II trials showing improved overall survival. With better understanding of the body’s immune system as well as advancements in vaccine development, the use of vaccines to target lung cancer cells in both non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) has shown promise but also challenges in the setting of advanced stage cancers, tumor resistance mechanisms, immune evasion, and tumor heterogeneity. The proposed solution is to enroll patients in the early stages of the disease, rather than waiting until progression occurs. Additionally, future efforts will focus on the targeted identification of specific and novel tumor neo-antigens. This review offers discussion and analysis of both completed and ongoing trials utilizing different strategies for vaccine development in relation to treating lung cancer as well as current challenges faced.